Illegal use of child soldiers - a neglected question in the preparation of professional soldiers - Jana Burešová (Vojenské rozhledy, 2017)
Use of child soldiers by rebel armed forces has been growing in recent years. In comparison to preceding conflicts, main reasons for their use have changed significantly – at the present time, children have become highly efficient psychological weapon in battles against the military from developed countries. This may have momentous consequences not only for the given children but also for professional soldiers. Fighting against child soldiers can indisputably affect the soldiers’ capability to discharge their duties. Furthermore, they have to cope with many individual moral dilemmas. The article will look into potential moral aspects regarding confrontation between child soldiers and members of professional armed forces. In the following section, training of professional soldiers and preparation of military mission will be explored. Subsequently, weaknesses which are crucial to forestall in the future will be outlined.